Service evaluation of a Specialist Memory Clinic for adults with ID in South Wales. Issue 4 (3rd July 2017) - Bayley, Amanda; Amoako, Annika; El-Tahir, Mohamed Omer
Abstract : Purpose: The purpose of this paper is to discuss the findings of a service evaluation project of the Specialist Memory Clinic for people with intellectual disabilities in South Wales using the Dementia guidelines published by the British Psychological Society and the Royal College of Psychiatrists (BPS/RCPsych, 2015). Design/methodology/approach: Clinical audit using case notes of patients attending Memory Clinics during 2011 and 2015 benchmarked against best practice guidelines; carers feedback from Memory Clinic attendance; and evaluation of the training sessions to carers. Findings: Audit findings show full compliance with standards (100 per cent) except for the baseline assessment for people with Down syndrome. Carer's evaluation and feedback was positive and constructive. Training evaluation indicates improvement in knowledge and positively received sessions. Research limitations/implications: The small number of people included and possibility of high motivated team may affect the service evaluation result. Practical implications: It is possible for the Community Learning Disability team to meet the standards published (BPS/RCPsych, 2015) through multidisciplinary working. Originality/value: Initial service evaluation completed after published guidelines for Dementia care by the BPS/RCPsych (2015).